Clinical analysis of leucine-rich glioma inactivated-1 protein antibody associated with limbic encephalitis onset with seizures. Issue 28 (July 2016) - Li, Zhimei; Cui, Tao; Shi, Weixiong; Wang, Qun
Abstract : Abstract: We summarized the clinical characteristics of patients presenting with seizures and limbic encephalitis (LE) associated with leucine-rich glioma inactivated-1 protein antibody (LGI1) in order help recognize and treat this condition at its onset. We analyzed clinical, video electroencephalogram (VEEG), magnetic resonance imaging (MRI), and laboratory data of 10 patients who presented with LGI1-LE and followed up their outcomes from 2 to 16 (9.4 ± 4.2) months. All patients presented with seizures onset, including faciobrachial dystonic seizure (FBDS), partial seizure (PS), and generalized tonic-clonic seizure (GTCS). Four patients (Cases 3, 5, 7, and 8) had mild cognitive deficits. Interictal VEEG showed normal patterns, focal slowing, or sharp waves in the temporal or frontotemporal lobes. Ictal VEEG of Cases 4, 5, and 7 showed diffuse voltage depression preceding FBDS, a left frontal/temporal origin, and a bilateral temporal origin, respectively. Ictal foci could not be localized in other cases. MRI scan revealed T2/fluid-attenuated inversion recovery (FLAIR) hyperintensity and evidence of edema in the right medial temporal lobe in Case 3, left hippocampal atrophy in Case 5, hyperintensities in the bilateral medial temporal lobes in Case 7, and hyperintensities in the basal ganglia and frontal cortex in Case 10. All 10 serum samples were positive for LGI1 antibody, but it was only detected in the cerebrospinal fluid (CSF) of 7 patients. Five patients (Cases 2, 4, 6, 7, and 8) presented with hyponatremia. One patient (Case 2) was diagnosed with small cell lung cancer. While responses to antiepileptic drugs (AEDs) were poor, most patients (except Case 2) responded favorably to immunotherapy. LGI1-LE may initially manifest with various types of seizures, particularly FBDS and complex partial seizures (CPS) of mesial temporal origin, and slowly progressive cognitive involvement. Clinical follow-up, VEEG monitoring, and MRI scan are helpful in early diagnosis. Immunotherapy is effective for the treatment of both seizure and LE associated with LGI1 antibody. Although mostly nonparaneoplastic, tumor screening is recommended in some cases.